Sistem Informasi Absensi Pegawai Menggunakan Metode RAD dan Metode LBS Pada Koordinat Absensi - Mohammad Arya Rosyd Sikumbang; Roni Habibi; Syafrial Fachri Pane (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Attendance can be said to be a presence data collection that is part of reporting activities that exist within an institution. A company requires a policy, especially the level of employee discipline. Discipline from employees is the main benchmark in seeing employee performance based on his presence in the company. A company must have a staff attendance system that can manage employee attendance based on obligations, prohibitions, and sanctions if an employee's obligations are not obeyed or violated. The problem that often occurs at the Bandung Central Statistics Agency is when employees are assigned to take a business trip, often the employee does not attend first to the office. By applying the Rapid Application Development (RAD) method, a method of software development with an object-oriented approach to system development, this method shorten the time in planning, designing, and implementing a system compared to traditional methods. Then the Location Based Service (LBS) method is used to access geographical information services used by users with mobile phone devices through cellular network connections to map locations to determine where the location of the user is. Thus, the existence of this research can help companies and employees in performing their performance without being bothered by pressure of workload.